Determination of Uraniumand Thorium in Sandstone Uranium Deposits by Inductively Coupled Plasma-Optical Emission Spectrometry with Microwave Digestion - ZHANG Lijuan; FANG Pengda; WANG Liqiang; WANG Jiasong (Yankuang ceshi, 2022)
BACKGROUND Sandstone-type uranium deposits are important strategic mineral resource. Rapid and accurate analysis of uranium and thorium content is of great significance to the evaluation and comprehensive utilization of this type of deposit. At present, the analysis of uranium and thorium is mainly determined by acid dissolution and alkali fusion methods to decompose samples. For the open acid dissolution method, the decomposition is often incomplete, resulting in lower results. The alkali fusion process is lengthy, which is not conducive to rapid detection. In addition, the high content of iron elements in sandstone type uranium deposits interfere with the measurement of uranium and thorium. OBJECTIVES To develop a method which can determine uranium and thorium in sandstone uranium deposits by inductively coupled plasma-optical emission spectrometry (ICP-OES) with microwave digestion. METHODS The samples were treated by microwave digestion technology, EDTA and triethanolamine mixed solution were added to the hydrochloric acid extract as masking agents to form a complex with iron ions in the solution, which effectively eliminated the interference of coexisting elemental iron on the determination of uranium and thorium. The experiment optimized the analytical spectral lines of each element, compared the amount of masking agent to obtain the best conditions, and basically eliminated the spectral line interference of coexisting elements by using the interference correction coefficient method. RESULTS The linear correlation coefficients of standard curves were greater than 0.9995, and the detection limit of uranium and thorium were 0.70μg/g, and 0.58μg/g, respectively. The relative error of the determination results of reference materials was 1.47%-1.82% and the relative standard deviation (RSD, n=12) was 1.32%-1.78%. CONCLUSIONS The method is simple to operate, effectively masking the interference of iron on uranium and thorium, and can be used to accurately complete the simultaneous determination of uranium and thorium in sandstone-type uranium deposits.